A Tribute to Lebanese Women Resistance Fighters - Aghacy, Samira (2000)
After twenty-five years of armed struggle against Israeli occupation, Lebanon has finally been liberated through the sacrifices of the Lebanese resistance and the Lebanese people. In this context, one could say that the role of women in the resistance cannot be underestimated. In a film entitled Zahrat alKandoul ("Women from South Lebanon") directed by May Masri and Jean Chamoun on the Lebanese resistance activist Khadija Herez, the latter tells us that there was no way women could have extricated themselves from the conflict.